The effect of Nd:YAG laser treatment of posterior capsule opacification on anterior chamber depth and refraction in pseudophakic eyes - Khambhiphant B (Dove Medical Press, 2015)
Bharkbhum Khambhiphant,1 Chayata Liumsirijarern,2 Piyada Saehout1 1Department of Ophthalmology, King Chulalongkorn Memorial Hospital, Thai Red Cross Society, 2Department of Ophthalmology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand Purpose: This was a prospective descriptive study to determine the changes in intraocular lens (IOL) position after neodymium-doped yttrium–aluminum–garnet (Nd:YAG) laser posterior capsulotomy by measuring anterior chamber depth (ACD) and refraction, including the spherical equivalent (SE) and cylinder. Materials and methods: Forty-seven pseudophakic eyes with posterior capsule opacification of 29 patients were included. Nd:YAG laser posterior capsulotomy was performed. Patients’ ACD and refraction were measured before the treatment, as well as after the treatment at 1 week and 3 months. IOLMaster® and an automated refractometer were used at the Department of Ophthalmology, King Chulalongkorn Memorial Hospital, Bangkok, Thailand. Results: There were no statistically significant differences in ACD and SE before and after laser treatment at 1 week and 3 months (repeated analysis of variance, P=0.582 and P=0.269, respectively). Both backward IOL movement (number [n]=29) and forward IOL movement (n=18) were found. Some changes in cylindrical refraction were found at 1 week, but decreased at 3 months after capsulotomy (baseline cylinder: -1.16; cylinder at 1 week and 3 months: -1.00 and -1.14, respectively; P=0.012). These changes were the same with one-piece and three-piece IOLs. Conclusion: Nd:YAG laser posterior capsulotomy did not significantly change ACD and SE. It led to cylinder change at 1 week after laser, but the effect decreased at 3 months. This effect was small and may not be clinically significant. Keywords: posterior capsule opacification, neodymium-doped yttrium–aluminum–garnet, anterior chamber depth, pseudophakia, refraction